Mesenteric Ischemia in a Patient with COVID-19 Infection - Yogesh KUKREJA; Zenith MOHANTY; Shishir KUMAR; Sanjog TRIPATHY (Modern Medicine)
The novel COVID-19 disease, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus, apart from its respiratory complications and coagulopathy, is also involved in damage to other organ systems. We present a report of presumptive case of COVID-19 positive patient with no respiratory symptoms with superior mesenteric vein and portal vein thrombosis along with acute intestinal ischemia. The patient underwent exploratory laparotomy, resection of the ischemic bowel loops with proximal ileostomy and distal mucous fistula. The case highlights that despite the absence of respiratory symptoms, patients infected with SARS-CoV-2 may show atypical presentations, such as gastrointestinal symptoms.